2013
DOI: 10.5455/msm.2013.25.9-13
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, Clinical and Laboratory Features of Rotavirus Gastroenteritis in Children Treated in Pediatric Clinic

Abstract: Aim:The aim of work was presentation of several socio-demographic, clinical and laboratory characteristics of gastroenteritis caused by rotavirus.The examinees and methods:The examinees were children under the age of five years treated at the Pediatric Clinic due to acute gastroenteritis caused by rotavirus. Rotavirus is isolated by method chromatographic immunoassay by Cer Test Biotec.Results:From the total number of patients (850) suffering from acute gastroenteritis, feces test on bacteria, viruses. protozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Proportion of male and female patients were 53% and 47% respectively in a study done by Azemi M et al in Kosovo 7 . In our study we found that 40% of cases with rotavirus diarrhoea were seen from October-December and 31% from July-September.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Proportion of male and female patients were 53% and 47% respectively in a study done by Azemi M et al in Kosovo 7 . In our study we found that 40% of cases with rotavirus diarrhoea were seen from October-December and 31% from July-September.…”
Section: Discussionmentioning
confidence: 88%
“…Azemi M et al in 2012 also observed no electrolyte abnormality in 64.1% patients. Only 9.85% of patients suffered hypernatremia 7 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…When many rotavirus studies carried out nationally as well as internationally are examined, it is clearly seen that information about laboratory features is very limited. In a study in which childhood gastroenteritis were assessed, it was reported that the most common laboratory findings were metabolic acidosis (47.17%), hypernatremia (9.89%) and high level of urea (31.07%) (24). In a study done in Turkey, on the other hand, metabolic acidosis (3.5%) and prerenal failure (4.5%) were reported to be the most common laboratory findings (25).…”
Section: Discussionmentioning
confidence: 99%